Morfoanatomía en Cranichideae (Orchidaceae) de la Estación Loma Redonda del Parque Nacional "Sierra Nevada", Mérida, Venezuela - Dugarte Corredor, Blanca; Luque Arias, Rebeca (Lankesteriana: International Journal on Orchidology, 2012)
A morpho-anatomic study of vegetative organs and peduncle was conducted in three representatives of the subtribe Cranichidinae s.l. (Orchidaceae): Aa paleacea, Myrosmodes paludosa, Pterichis multiflora of the Sierra Nevada National Park in Merida, Venezuela at Loma Redonda Cable car station. These three species were studied with the aim of determining possible diagnostic characters and adaptations to the paramo. Adult plants were collected. Shared characters were determined: gross root, monostratified velamen and exodermis, exodermis scalariform with thickenings in radial walls, spiranthosomes in the cortex and glabrous clustered leaves. Differentiated mesophyll is reported for the first time in Cranichideae. The diagnostic characters determined were: thickness of cortex root; number of runs of the palisade and of the spongy; in the peduncle different types of steles. Some of following characters are considered adaptive to the environment: gross root, compact cortex, small shiny leaves of thick cuticle, development of palisade; peduncle with cuticle and thick epidermis. Myrosmodes paludosa was considered the most xeromorphic species. A key using morphological and anatomical characters is presented.